2020
DOI: 10.3390/ani10030401
|View full text |Cite
|
Sign up to set email alerts
|

Improvements on Live Feed Enrichments for Pikeperch (Sander lucioperca) Larval Culture

Abstract: This study focused on supplementing pikeperch (Sander lucioperca) larvae with rotifers fed with Chlorella vulgaris during the first 15 days post hatching (dph). Larvae were fed a combination of rotifers and artemia under three different enrichments: A) Nannochloropsis occulata, B) Chlorella vulgaris, and C) a commercial enrichment—Selco, Spresso from INVE. After 17 days from the trial initiation differences were found between treatments on survival rate, myomere height (MH), fatty acid composition, and stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
(62 reference statements)
3
17
1
Order By: Relevance
“…Te choice of gutpriming agents was based on positive fndings in other fsh species. For instance, the administration of lactic acid bacteria, similar to the ones present in Bactocell, improved growth, immunity, and health status as well as reproduction in zebrafsh, Danio rerio [45,46]; increased survival rates in pikeperch, Sander lucioperca larvae [47]; improved stress resistance in Persian sturgeon, Acipenser persicus larvae [48]; and induced higher activity of digestive enzymes in juvenile California halibut, Paralichthys californicus [49]. Moreover, the use of compounds present in AgriMOS has improved growth performance, survival, and immune status of rainbow trout, Oncorhynchus mykiss [50], or enhanced growth performance and feed utilization of the giant freshwater prawn, Macrobrachium rosenbergii juveniles [51].…”
Section: Discussionmentioning
confidence: 99%
“…Te choice of gutpriming agents was based on positive fndings in other fsh species. For instance, the administration of lactic acid bacteria, similar to the ones present in Bactocell, improved growth, immunity, and health status as well as reproduction in zebrafsh, Danio rerio [45,46]; increased survival rates in pikeperch, Sander lucioperca larvae [47]; improved stress resistance in Persian sturgeon, Acipenser persicus larvae [48]; and induced higher activity of digestive enzymes in juvenile California halibut, Paralichthys californicus [49]. Moreover, the use of compounds present in AgriMOS has improved growth performance, survival, and immune status of rainbow trout, Oncorhynchus mykiss [50], or enhanced growth performance and feed utilization of the giant freshwater prawn, Macrobrachium rosenbergii juveniles [51].…”
Section: Discussionmentioning
confidence: 99%
“…Although Artemia is a common diet in fish larviculture, the nutritional profile, size and inconsistent in biochemical composition, makes it less suitable candidate for first feeding. In this respect, recent studies showed the importance of larval first feeding with rotifers (Brachionus plicatilis) with a supplementation of microalgae to provide a better growth and higher survival (Yanes-Roca et al, 2018;Imentai et al, 2020;Yanes-Roca et al, 2020a;Yanes-Roca et al, 2020b). It was reported that higher growth and survival was reached when larvae fed with B. plicatilis at the beginning of exogenous feeding and afterwards replaced with Artemia or a combination of two during first feeding (Imentai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Docosahexaenoic acid is primarily incorporated into neural tissues, and deficiencies have been associated with noninflation of the swim bladder (Matsunari et al 2013), reduced stress tolerance (Lund et al 2012;Yanes-Roca et al 2020), impaired vision (Bell et al 1995), malpigmentation, and reduced growth and survival (Copeman et al 2002). Arachidonic acid is not as abundant as DHA and EPA in fish bodies (Copeman et al 2002), but it is also strongly associated with the larval stress response (Martins et al 2013), hormone production (Sargent et al 1995), and early life morphological development (Boglino et al 2012(Boglino et al , 2013.…”
mentioning
confidence: 99%
“…Many of the zooplankton species that are used as live feeds for larval fish, such as rotifers Brachionus plicatilis and brine shrimp Artemia franciscana nauplii, are deficient in or lacking the long‐chain (LC; 20–22‐carbon) polyunsaturated fatty acids (PUFAs) that are needed to support rapid growth and healthy development (Copeman et al 2002; Ritar et al 2004; Kotani et al 2010). These essential fatty acids impact early physiological and neurological differentiation/metamorphosis, and dietary deficiencies are associated with impaired stress response, impaired brain development, abnormal swimming behavior, and mortality (Lund et al 2012; Yanes‐Roca et al 2020). Long‐chain PUFAs, such as docosahexaenoic acid (DHA; 22:6[n‐3], where the number to the left of the colon is the number of carbon atoms, the number immediately to the right of the colon is the number of double bonds, and the number after the hyphen is the position of the first double bond from the methyl end), arachidonic acid (ARA; 20:4[n‐6]), and eicosapentaenoic acid (EPA; 20:5[n‐3]), serve essential roles in cell membrane fluidity and function (Tocher 2010).…”
mentioning
confidence: 99%